2023
DOI: 10.1186/s12912-023-01202-2
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators in the implementation of mobilization robots in hospitals from the perspective of clinical experts and developers

Abstract: Background Early mobilization can help reduce severe side effects such as muscle atrophy that occur during hospitalization. However, due to time and staff shortages in intensive and critical care as well as safety risks for patients, it is often difficult to adhere to the recommended therapy time of twenty minutes twice a day. New robotic technologies might be one approach to achieve early mobilization effectively for patients and also relieve users from physical effort. Nevertheless, currently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This differs from other trials in which either nurses or physiotherapists were explicitly assigned to perform the intervention, or the safety of the intervention was tested in feasibility studies (Bertelsen et al, 2020;Gandolfi et al, 2017). To make robot-assisted mobilization an intervention that saves human resources, two other factors should be taken into account: the training of core teams within a unit, indicated in our preliminary research (Warmbein et al, 2023) as well as the need to develop technology that is easy to use in practice, highlighted by Bertelsen et al (2020). However, Brinkmann et al (2022) observed that the implementation of robotic systems for manual patient handling can alleviate physical workload and musculoskeletal strain for nurses.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This differs from other trials in which either nurses or physiotherapists were explicitly assigned to perform the intervention, or the safety of the intervention was tested in feasibility studies (Bertelsen et al, 2020;Gandolfi et al, 2017). To make robot-assisted mobilization an intervention that saves human resources, two other factors should be taken into account: the training of core teams within a unit, indicated in our preliminary research (Warmbein et al, 2023) as well as the need to develop technology that is easy to use in practice, highlighted by Bertelsen et al (2020). However, Brinkmann et al (2022) observed that the implementation of robotic systems for manual patient handling can alleviate physical workload and musculoskeletal strain for nurses.…”
Section: Discussionmentioning
confidence: 97%
“…For this purpose, a three-year research project was initiated. Prior to that, a comprehensive preliminary study was carried out, which focused on the current state of early mobilization in intensive care units and the experience gained to date with the implementation of robotic systems (Huebner et al, 2022;Klamt et al, 2021;Warmbein et al, 2023;Mehler-Klamt et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…In the process of operationalising the phenomena "perception of psychological and physical stress", the standardised observation sheet was initially created. Preparation was based on a previously conducted systematic literature research and evaluation of the preliminary studies performed within the framework of the MobiStaR project (9,11,18) . The relevant variables and their variations were identi ed before designing the observation sheet.…”
Section: Data Collection and Evaluationmentioning
confidence: 99%
“…Moreover, high levels of stress can affect self-esteem and contribute to burnout (8). Robotic systems can be utilised, some of which can even assist or take over mobilisation activities to counteract patients' prolonged immobility and alleviate the workload of the mobilising specialist staff (9). One such robotic system is the adaptive robotic assistance system VEMOTION® developed by ReActive Robotics.…”
Section: Introductionmentioning
confidence: 99%
“…1.1.2 Mobilisation with the VEMOTION® robotic system VEMOTION®, an adaptive robotic assistance system, makes it possible to mobilise intensive-care patients in their hospital beds without having to transfer them to a therapy device (14). A robotic system can be docked to an adapted bed in which a patient is secured as shown in Fig.…”
Section: Conventional Mobilisationmentioning
confidence: 99%